The genus Canidia Thomson, 1857 (Coleoptera: Cerambycidae, Lamiinae, Acanthocinini) - Wappes, James E.; Lingafelter, Steven W. (Zootaxa, 2005)
The lamiine genus Canidia Thomson is redefined with Canidiopsis Dillon and Pseudocanidia Dillon as new synonyms. Three new species from Mexico are described and illustrated: Canidia chemsaki, C. giesberti, and C. turnbowi. The following new synonymies are proposed: Canidiopsis similis Dillon, 1955 and Canidiopsis hebes Dillon, 1955 = Canidia mexicana Thomson, 1860; Pseudocanidia cuernavacae Dillon, 1955 = Dectes spinicornis Bates, 1881; and Dectes (Canidia) balteata var. inapicalis Tippmann, 1960 = Dectes balteatus Lacordaire, 1872. A key to the eight species and one subspecies is presented.